Hot dog - Salati, Doug (New York : Alfred A. Knopf, 2022)
A summery picture book about mindfulness, featuring an overheated--and overwhelmed--canine in need of sea, sand, and fresh air.
Horn Book Starred, November 2022
Pub Weekly, February 2022
Kirkus Starred, September 2022
2.4
Caldecott Medal/Honor, 2023
K-3
Keywords: Senses and sensation -- Juvenile fiction; Dogs -- Juvenile fiction; Senses and sensation -- Fiction; Dogs -- Fiction; Animal fiction